Pengaruh Opinion Shopping, Prior Opinion, Debt Default, Terhadap Opini Going Concern yang dimoderasi Komite Audit - Melvin; Dade Nurdiniah (UNIVERSITAS KALBIS, 2022)
This research aims to analyze the influence of opinion shopping, prior opinion, and debt default on going concern opinion with the audit committee as moderating. The population used in this research were all service companies listed on the Indonesia Stock Exchange (IDX) in the period 2015 - 2018 with a sample selection technique using a purposive sampling method. The number of research samples are 67 companies and 268 research samples. Data analysis methods used logistic regression and moderated regression analysis using the SPSS version 25 program. The results of this research indicate that opinion shopping doesn’t have influence on going concern opinion, while prior opinion and debt default have a positive influence on going concern opinion. The audit committee can moderate opinion shopping towards going concern opinion but cannot moderate prior opinion and debt default towards going concern opinion.